Assessment of poverty among urban farmers in Ibadan metropolis, Nigeria (2008)
This study examined poverty status of urban farm households. The study was carried out in Ibadan metropolis. The data used for the study were obtained from well-structured questionnaires. 200 farming households were sampled from two local government areas within Ibadan metropolis. Data generated were analysed using descriptive statistics, poverty indices and logistics regression analysis. Results from the study showed that those engaged in crop farming have the highest poverty level (50%), while mixed farming households have poverty level of 37% and livestock, 17%. The estimated logistic regression equation showed that crop farming activity engaged in and household size increase the odd ratio of being poor while age of urban farmers, educational status, years of experience in farming and livestock farming decrease the odd ratio of being poor. Hence, mixed farming and livestock farming are antidote to reducing poverty among urban farmers.